DETERMINAN KETIMPANGAN ANTAR WILAYAH JAWA TIMUR - Kaimuddin, Abd Muis (Jurnal Cita Ekonomika, 2024)
The purpose of this study is to analyze the factors that cause inequality in East Java. The method used in this study is multiple linear regression to see the effect of the independent variable on the dependent variable and LQ (Location Quotient) analysis to measure agglomeration using 38 district / city data in the 2017-2020 period. Based on the partial test results, it is found that agglomeration and economic growth has a positive and significant effect. Education has a negative and significant effect on inequality. Meanwhile, unemployment has no effect on inequality. The results of the LQ analysis found that there are eight regions that have leading sectors in the industrial sector.